2007
DOI: 10.1016/j.cellimm.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

An adenoviral vector encoding dominant negative Cbl lowers the threshold for T cell activation in post-thymic T cells

Abstract: Cbl family ubiquitin ligases act as key negative regulators of TCR signaling. Knockout mice lacking Cbl-b and c-Cbl show augmented T cell activation and CD28-independent IL-2 production. In order to study Cbl function directly in post-thymic T cells, a DN Cbl adenovirus was generated for transduction of T cells from Coxsackie/adenovirus receptor (CAR) transgenic (Tg) mice. We show that dominant negative (DN) Cbl-transduced CD4 + T cells exhibited enhanced IL-2 production upon TCR/CD28 engagement compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
1
12
1
Order By: Relevance
“…Recent studies have shown that the ubiquitin ligase c-Cbl is a negative regulator of the MAPK/ERK pathway. 23 Our data show that IFNα alone significantly reduced c-Cbl protein levels after 48 and 72 h (Fig. 5A), which coincided with the increased expression of p-ERK (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Recent studies have shown that the ubiquitin ligase c-Cbl is a negative regulator of the MAPK/ERK pathway. 23 Our data show that IFNα alone significantly reduced c-Cbl protein levels after 48 and 72 h (Fig. 5A), which coincided with the increased expression of p-ERK (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…20 It not only plays an essential role in sequestering signaling molecules from lipid rafts but also negatively regulates tyrosine kinase-mediated growth factor receptor signaling through ubiquitination and degradation of numerous signaling proteins. [21][22][23] In CD4 + T lymphocytes, transduction with dominant negative c-Cbl increases anti-CD3/CD28-induced phosphorylation of ERK, suggesting that c-Cbl could negatively regulate ERK activity. 23 However, whether c-Cbl is involved in the synergistic effects of IFNα and TRAIL on apoptosis induction is unclear.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation
“…For example, T cells transduced to express a dominant-negative form of Cbl-b or that are deficient for SHP-1 (SH2-containing protein tyrosine phosphatase-1) exhibit an augmented T cell response to antigen (Lorenz et al, 1996;Fawcett and Lorenz, 2005;Zha and Gajewski, 2007), and preliminary studies with T cells deficient for either of these molecules have suggested increased efficacy in vivo (our unpublished data).…”
Section: Methods For Increasing Aviditymentioning
confidence: 94%
“…The adoptive transfer of T cells appears to be a promising new treatment for various types of cancer (31,32) and several strategies to increase the functional avidity of the TCR that target the binding of antigen at the cell surface have been proposed (33)(34)(35)(36). An alternate approach would be to manipulate intracellular signaling pathways that normally act to attenuate T-cell signaling such as those mediated by Cbl-b and SHP-1 (37)(38)(39). The data presented here show that introduction of a LAT molecule resistant to ubiquitylation is another option by which to augment T-cell potency.…”
Section: Discussionmentioning
confidence: 99%